In vitro exposure to Hymenoptera venom and constituents activates discrete ionotropic pathways in mast cells. Issue 1 (1st January 2019) - Jansen, C.; Shimoda, L. M.N.; Starkus, J.; Lange, I.; Rysavy, N.; Maaetoft-Udsen, K.; Tobita, C.; Stokes, A.J.; Turner, H
ABSTRACT: Calcium entry is central to the functional processes in mast cells and basophils that contribute to the induction and maintenance of inflammatory responses. Mast cells and basophils express an array of calcium channels, which mediate responses to diverse stimuli triggered by small bioactive molecules, physicochemical stimuli and immunological inputs including antigens and direct immune cell interactions. These cells are also highly responsive to certain venoms (such as Hymenoptera envenomations), which cause histamine secretion, cytokine release and an array of pro-inflammatory functional responses. There are gaps in our understanding of the coupling of venom exposure to specific signaling pathways such as activation of calcium channels. In the present study, we performed a current survey of a model mast cell line selected for its pleiotropic responsiveness to multiple pro-inflammatory inputs. As a heterogenous stimulus, Hymenoptera venom activates multiple classes of conductance at the population level but tend to lead to the measurement of only one type of conductance per cell, despite the cell co-expressing multiple channel types. The data show that ICRAC, IARC, and TRPV-like currents are present in the model mast cell populations and respond to venom exposure. We further assessed individual venom components, specifically secretagogues and arachidonic acid, and identified the conductances associated with these stimuli in mast cells. Single-cell calcium assays and immunofluorescence analysis show that there is heterogeneity of channel expression across the cell population, but this heterogeneity does not explain the apparent selectivity for specific channels in response to exposure to venom as a composite stimulus.